Clickbait Journalism: Media Logics in Journalism Practices on Online Media - Fakhruroji, Moch; Suryana, Cecep; Wahyudin, Aep (Communicatus: Jurnal Ilmu komunikasi, 2023)
This article will examine the practice of clickbait journalism, which is increasingly common in news titles in online media, through the lens of Altheide and Snow's media logic. Due to social distancing policies during the pandemic, this article employs the library research method by collecting materials and references online by observing several clickbait news titles on Tribunnews.com. Trends can be identified based on data analysis, such as exaggeration, graphics or titles containing obscene, disturbing/disgusting, or shady material, bait-and-switch, and ambiguous or confusing and tend to grab readers' interest. Nevertheless, although this practice has been criticized as a mere business, this article argues that this practice does not always represent the poor credibility of online media since this practice is not only caused by the technical logic of online media but also caused by the changing behavior of the readers which is more increasingly digitalized.